Motor Cortex Neuroplasticity Following Brachial Plexus Transfer - Dimou, Stefan; Biggs, Michael; Tonkin, Michael; Hickie, Ian B.; Lagopoulos, Jim (Frontiers in Human Neuroscience, 2013)
In the past decade, research has demonstrated that cortical plasticity, once thought only to exist in the early stages of life, does indeed continue on into adulthood. Brain plasticity is now acknowledged as a core principle of brain function and describes the ability of the central nervous system to adapt and modify its structural organization and function as an adaptive response to functional demand. In this clinical case study we describe how we used neuroimaging techniques to observe the functional topographical expansion of a patch of cortex along the sensorimotor cortex of a 27 year-old woman following brachial plexus transfer surgery to re-innervate her left arm. We found bilateral activations present in the thalamus, caudate, insula as well as across the sensorimotor cortex during an elbow flex motor task. In contrast we found less activity in the sensorimotor cortex for a finger tap motor task in addition to activations lateralised to the left inferior frontal gyrus and thalamus and bilaterally for the insula. From a pain perspective the patient who had experienced extensive phantom limb pain before surgery found these sensations were markedly reduced following transfer of the right brachial plexus to the intact left arm. Within the context of this clinical case the results suggest that functional improvements in limb mobility are associated with increased activation in the sensorimotor cortex as well as reduced phantom limb pain.